IMPROVING VOCATIONAL TEACHERS’ INNOVATIVENESS THROUGH PERSONALITY AND TRANSFORMATIONAL LEADERSHIP DEVELOPMENT - Thahir, Muthahharah; Komariah, Aan; Sunaengsih, Cucun; Rahmawati, Ima (Universitas Pendidikan Indonesia, 2022)
The success of a vocational school in achieving its goals is greatly determined by how innovative the school members, which include teachers as frontliners in educational quality, are. Innovativeness does not emerge and develop in vacuum. It is closely related to other factors such as personality and transformational leadership. 238 private vocational high school teachers in Bogor City were selected as sample in the present study, which implemented quantitative approach using survey method.Based on the findings, it was concluded that: (1) there was a positive correlation between personality and innovativeness, with coefficient of correlation (ry1) of 0.318 and coefficient of determination (ry12) of 10.14% through regression equation Ŷ = 47.669 + 0.597X1, (2) there was a positive correlation between transformational leadership and innovativeness, with coefficient of correlation (ry2) of 0.261 and coefficient of determination (ry22) of 6.83% through regression equation Ŷ = 84.113 + 0.207X2,and (3) there was a positive correlation between personality and transformational leadership variables, collectively, and innovativeness variable, with coefficient of correlation (ry12) of 0.379 and coefficient of determination (ry122) of 14.37% through regression equation Ŷ = 33.492 + 0.165X1 + 0.524X2. Teachers’ innovativeness can be improved through personality development. The roles of headmasters’ transformational leadership will modify teachers’ behavior, allowing the latter to work more than what is expected and to improve their performance. It is a form of teachers’ empowerment to develop skills and trusts, and to create a better school culture that encourage innovativeness and creativity development. In other words, personality and transformational leadership development can improve teachers’ innovativeness.